The Socialist Car : Automobility in the Eastern Bloc - Siegelbaum, Lewis H. (Book collections on Project MUSE., 2011)
In 'The Socialist Car' eleven scholars from Europe and North America explore the interface between the motorcar and the state in the socialist countries of Eastern Europe.